Вязаные цветы - Бобрицкая Елена Сергеевна (Простейший способ, 2015)
Экземпляры: ф.20 (20160315) / Инвентарный номер: 52743 / Цена: 73.00. / Сис.шифр: 37.248 / Авт.знак: Б 72 / ГРНТИ: 75.35 / ББК: 37.248